Statin Use Is Associated With a Lower Risk of Blepharitis: A Population-Based Study - Feng, Kathy Ming; Chung, Chi-Hsiang; Chen, Yi-Hao; Chien, Wu-Chien; Chien, Ke-Hung (Frontiers in Medicine, 2022)
Background: Blepharitis is a common eye disorder that may be overlooked by patients and clinical practitioners. The symptoms of blepharitis often manifest as irritation, a burning sensation, grittiness, and itchiness and may decrease visual acuity if not treated promptly. Meibomian gland dysfunction (MGD), a common cause of blepharitis, is believed to be associated with increased inflammatory marker levels that may disrupt the composition of lipids produced by the sebaceous glands in the eyelids and ultimately cause tear film instability. Methods: This is a retrospective, population-based study using National Health Insurance Research Database (NHIRD) data from a 14-year period (2000-2015). Pearson chi-squared and Student’s t-tests were used to assess the differences in categorical and continuous variables, respectively, between statin users and nonstatin users. Univariate and multivariate Cox regression analyses were performed to calculate the hazard ratios (HRs) after adjusting for confounders. Kaplan-Meier analysis was used to assess the cumulative risk of blepharitis between the two cohorts. Results: A total of 67,014 patients who used statins were enrolled as the study cohort, and 268,056 patients who did not use statins were enrolled as the comparison cohort. The incidence of blepharitis was 3.04% with statin treatment and 3.72% without statin treatment (p<0.001). Patients who used statins had a lower risk of developing blepharitis (adjusted hazard ratio (aHR): 0.746, p<0.001) than those who did not. In addition, diabetes mellitus (DM), hypertension, coronary heart disease (CHD), stroke, chalazion, rosacea, Sjogren syndrome, psoriasis and atopy were found to be possible risk factors for blepharitis. Conclusion: Statin use can decrease the risk of developing blepharitis. However, further prospective studies are needed to evaluate statin treatment for various subtypes of blepharitis and to identify the associated mechanism.